Simple Hybrid Scaling-Free CORDIC Solution for FPGAs. (24th April 2014) - Moroz, Leonid; Nagayama, Shinobu; Mykytiv, Taras; Kirenko, Ihor; Boretskyy, Taras
Abstract : COordinate Rotation DIgital Computer (CORDIC) is an effective method that is used in digital signal processing applications for computing various trigonometric, hyperbolic, linear, and transcendental functions. This paper presents the theoretical basis and practical implementation of circular (sine-cosine) CORDIC-based generator. Synthesis results of this generator based on Altera Stratix III FPGA (EP3SL340F1517C2) using Quartus II version 9.0 show that the proposed hybrid FPGA architecture significantly reduces latency (42% reduction) with a small area overhead, compared to the conventional version. The proposed algorithm has been simulated for sine and cosine function evaluation, and it has been verified that the accuracy is comparable with conventional algorithm.